Integrating Internet in teaching Arabic language: a new approach of teaching Arabic language - Ahmed, Ibrahim (LAP LAMBERT Academic Publishing AG & Co. KG, 2010)
This book is a unique in integrating the Internet in teaching Arabic language. The book is about the theoretical and practical framework of teaching Arabic via the website. It emphasises on the practical work from the field of teaching. It uses modern sophisticated technology in the class e.g. (new group, Websites as well as email). The book will be considered as a reference for the university students.